2015
DOI: 10.1002/ece3.1732
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, nitrogen, and phosphorus storage in alpine grassland ecosystems of Tibet: effects of grazing exclusion

Abstract: In recent decades, alpine grasslands have been seriously degraded on the Tibetan Plateau and grazing exclusion by fencing has been widely adopted to restore degraded grasslands since 2004. To elucidate how alpine grasslands carbon (C), nitrogen (N), and phosphorus (P) storage responds to this management strategy, three types of alpine grassland in nine counties in Tibet were selected to investigate C, N, and P storage in the environment by comparing free grazing (FG) and grazing exclusion (GE) treatments, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 75 publications
2
45
2
Order By: Relevance
“…, Lu et al. , b). In other ecosystems, there is growing evidence that complete exclusion from grazing for a prolonged period of time may not lead to an improvement in vegetation and soil conditions (Chaneton and Lavado , Hart and Scientist , Firincioğlu et al.…”
Section: Discussionmentioning
confidence: 98%
“…, Lu et al. , b). In other ecosystems, there is growing evidence that complete exclusion from grazing for a prolonged period of time may not lead to an improvement in vegetation and soil conditions (Chaneton and Lavado , Hart and Scientist , Firincioğlu et al.…”
Section: Discussionmentioning
confidence: 98%
“…The suitable time for plant growth and development only lasts 2–4 months, which does not promote the accumulation of AGB (Li, Wang, An, & Ji, ). In addition, soil could also affect the vegetation productivity, community composition, and plant species richness by supplying organic matter and cycling nutrients, such as nitrogen and carbon (Lu et al, 2015; Lu, Yan, Sun, X. K. Zhangz et al, ). Many previous studies have demonstrated that GE varies several physical properties of soil (Greenwood & Mckenzie, ; Hoshino, Tamura, Fujimaki, & Asano, ; Medinaroldán, Pazferreiro, & Bardgett, ; Mofidi, Jafari, Tavili, Rashtbari, & Alijanpour, ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil water content (SWC) was measured using the drying method; soil organic carbon (SOC) and soil total nitrogen (STN) were determined using a vario MACRO cube elemental analyser (Elementar Analysensysteme GmbH, Hanau, Germany) (Lu et al, 2015); soil total phosphorus (STP) Soil samples were air-dried and handpicked to remove plant components in the field.…”
Section: Plant and Soil Propertiesmentioning
confidence: 99%